PERAN KEPALA KAMPUNG DALAM PEMBANGUNAN KAMPUNG NGENYAN ASA DI KECAMATAN BARONG TONGKOK KABUPATEN KUTAI BARAT - DORAN, AGUS FRANSISKO (PREDIKSI, 2016)
AgusFransisko Doran, The role of Head of KampungDalam Pembangunan KampungNgenyanAsa under the guidance of Mr. H.AhmadJubaidi, M.Si and Mrs. Jamiah, S. Sos, M.SiThe purpose of this study was to determine the role of village head in running the village development and to identify factors inhibiting the village head in carrying out development in KampungNgenyanAsa Barong Tongkok District West Kutai.Type of research included qualitative descriptive.The main focus of research defined the role of Head of Kampung indicators: governance, village development, develop the economic life of the community, village head inhibiting factor in implementing development in KampungNgenyanAsa districts Barong Tongkok West Kutai.While the source of the data taken from informen competent, among which: Kampung Secretary, Staff / Employee NgenyanAsaKampung Office whose duties related to the research problem under investigation and the public.While data collection techniques by observation, interviews, and documentation.Analysis of the data used is an interactive model developedThe results showed that the administration of the village and community development is done in the village hall.Realization of democracy in village administration official elements of village government.The village headman to supervise the implementation of the rules and regulations of the village chief.Government administration office is rarely open and difficult village chief in my hometown for ketemui if you want to take care of the home secretary of the village.Village Development is a deliberate change of the Head and the people in the village, in the form of facilities and infrastructure that can improve people's welfare as planned by the village head to the public.Economic life of the community in terms of economic and social order is good enough, either from outside or from within the village.Head of the village is a driving force of development in social and economic fields.means the existence of village headman function mobilize the community in doing something actions or activities to co-develop the economic life of the people in development.